The Enhancement of Students Mathematical Communication Ability Through RME-Textbook - Fevi Rahmawati Suwanto; Ariyadi Wijaya (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2021)
This study was a research and development used ADDIE model aimed to produce mathematics textbook for 8th-grade students by applying five principles of the Realistic Mathematics Education (RME) approach, included: phenomenological exploration, bridging by vertical instruments, self-reliance with students own constructions and productions, interactivity, and intertwining. The subject in this study involved 30 students' junior high school in Yogyakarta. The qualities of the developed textbook refer to three criteria, namely validity, practicality, and effectiveness. Supporting instruments used to examine three criteria for the quality of the textbook were validation sheets, assessment sheets for teachers and students, and students' mathematical communication ability test. The textbook meets the criteria of validity, practicality, and effectiveness if at least